A Systematic Review of the Utility of Indocyanine Angiography in Autologous Breast Reconstruction. Issue 5 (May 2021) - Parmeshwar, Nisha; Sultan, Steven M.; Kim, Esther A.; Piper, Merisa L.
Abstract : Background: In the last decade, a number of studies have demonstrated the utility of indocyanine green (ICG) angiography in predicting mastectomy skin flap necrosis for immediate breast reconstruction. However, data are limited to investigate this technique for autologous breast reconstruction. Although it may have the potential to improve free flap outcomes, there has not been a large multicenter study to date that specifically addresses this application. Methods: A thorough literature review based on Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines was conducted. All studies that examined the use of intraoperative ICG angiography or SPY to assess perfusion of abdominally based free flaps for breast reconstruction from January 1, 2000, to January 1, 2020, were included. Free flap postoperative complications including total flap loss, partial flap loss, and fat necrosis were extracted from selected studies. Results: Nine relevant articles were identified, which included 355 patients and 824 free flaps. A total of 472 free flaps underwent clinical assessment of perfusion intraoperatively, whereas 352 free flaps were assessed with ICG angiography. Follow-up was from 3 months to 1 year. The use of ICG angiography was associated with a statistically significant decrease in flap fat necrosis in the follow-up period (odds ratio = 0.31, P = 0.02). There was no statistically significant difference for total or partial flap loss. Conclusions: From this systematic review, it can be concluded that ICG angiography may be an effective and efficient way to reduce fat necrosis in free flap breast reconstruction and may be a more sensitive predictor of flap perfusion than clinical assessment alone. Future prospective studies are required to further determine whether ICG angiography may be superior to clinical assessment in predicting free flap outcomes.